Unraveling the Mystery of D (Discriminant): Intensive Community Service Program (PkM) for the Transformation of Conceptual Understanding of Quadratic Equations in Class X Students at SMA Negeri 1 Banyuwangi - Nawal Ika Susanti; Moh. Abdul Qohar; Luthfi Qothrun Nada (CENDEKIA: Jurnal Pengabdian Masyarakat, 2025)
This Community Service (PkM) activity addressed the conceptual gap in understanding the Discriminant of Quadratic Equations among 180 Grade X students at SMA Negeri 1 Banyuwangi. Students showed high procedural ability but poor interpretation of the discriminant's meaning ($D$), leading to low learning mastery and non-routine problem-solving skills. The intervention utilized Intensive Mentoring implementing the Problem-Based Learning (PBL) model supported by conceptual visualization. The PkM involved three stages: preparation, implementation (small-group mentoring and visual demos), and evaluation. Results showed a significant Transformation of Conceptual Understanding. Quantitatively, the students' average score increased by 32.6% (from 63.5 to 84.2), and the learning mastery percentage (KKM  75) sharply rose to 85%. Qualitatively, the activity successfully fostered critical thinking and collaboration in understanding the relationship between the value of $D$, the nature of the roots, and the quadratic function graph. It is concluded that Intensive Mentoring, emphasizing visualization and PBL, is an effective pedagogical strategy to resolve conceptual difficulties with the Discriminant, offering a structured solution for enhancing mathematics learning quality.